FinTech Monopoly and Systemic Risk: Evidence From China - Rui Wang; Zhihao He; Shunjing Yang (SAGE Open)
With the rapid development of FinTech, it is of great significance to gain comprehensive insights into its potential risks. This paper focuses on the financial risks brought by the FinTech monopoly. We take the listed FinTech companies in China as samples to build the FinTech monopoly index and the systematic risk indicator, and the effect of the monopoly of Fintech companies on systematic risk is next analyzed using the fixed effect model. The results indicate that the FinTech monopoly will aggravate the systemic risk. Subsequently, the heterogeneous factors for the above nexus are investigated based on the micro characteristics of FinTech companies and the macro environment. On this basis, the mechanism of the above effect is also analyzed, and it is shown that the FinTech monopoly impacts systemic risk mainly via inducing excessive consumption, increasing banks’ credit risk, and inhibiting the development of FinTech.